Designing the Concept of Start-up & Mentoring Profiling Inside New Normal University - Sasono Wibowo; Indra Gamayanto (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Start-ups are important pillars in improving people's lives, and many start-ups will certainly increase employment. Still, it must understand that start-ups should be limited to the business. Many start-ups have closed down due to a need for integrated management, human resources, capital, and so on; these require proper guidance to reach the highest level. This article complements the previous article, namely the Development of Mentoring Management in Producing High-Quality Human Resources at the University Level in Facing the ASEAN Economic Community (MEA) Using the Kiyosaki Concept Blanchard ABCD Trust Methods-HSOVA. This guidance is essential to maintain, improve and develop existing start-ups. With the accuracy of guidance, it is necessary so start-ups to turn on profit and develop human resources in communication, psychology, and more targeted life goals. This article's result is a profiling mentoring framework; in this framework, there will be guiding people who want to work in the start-up field. Furthermore, the maturity level of mentoring profiling is one part of this framework. This framework will be flexible, applied, and adapted to existing conditions during a pandemic.